ANALISIS PENGARUH KUALITAS LAYANAN, KUALITAS FUNGSIONAL, DAN KUALITAS TEKNIKAL TERHADAP KEPUASAN PELANGGAN (STUDI KASUS PADA SUZUKI MEDAN JAYA GROUP JL. KATAMSO NO 78 YOGYAKARTA) - Ulfah Yuliana (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2014)
This research aims to determine the effect of service quality , functional quality , and technical quality of the service user customer satisfaction Suzuki motorcycle servicing of Medan Jaya Group Yogyakarta. This research is a quantitative study descriptive research type. There are three independent variables , namely the quality of service, functional quality, and technical quality. While the dependent variable is customer satisfaction. The population in this study is customer of Suzuki Medan Jaya Group service motorcycle Katamso Number 78 Yogyakarta. Sample of 100 respondents using accidental sampling approaches. Based on the analysis of data obtained the following results : There is a simultaneous influence between the variables of service quality, functional quality, and technical quality of the service user customer satisfaction of Suzuki motorcycle servicing Medan Jaya Group Yogyakarta, the significant value of 0.000, with a regression equation Y = 0.148 X1 + 0.576 0.251 X2 + X3. There is a significant effect of the variable quality of service to customer satisfaction of Suzuki Motorcycle Medan Jaya Group Yogyakarta services with t value 2.359 with a significance value of 0.02. There is a significant effect of the variable functional quality to customer satisfaction of Suzuki Motorcycle Medan Jaya Group Yogyakarta services with t value 7.772 with a significance value of 0.000 . There is a significant effect of the variable technical quality to customer satisfaction of Suzuki Motorcycle Medan Jaya Group Yogyakarta services with t value 3.400 with significant value of 0.001 . Great contribution value of 69.4 % while the remaining 30.6 % is influenced by other factors . The results of the analysis using stepwise method showed that the functional quality dimension (X2) has the most dominant effect on customer satisfaction (Y) with a value of 10,017 t and a significant level of 0.000. Key words : quality of service , functional quality , technical quality and customer satisfaction.